De sociologie en de pandemie inzichten en vooruitblik na twee jaar coronacrisis - André, Stéfanie; Reeskens, Tim; Völker, Beate (Tilburg University Press, 2022)
The corona pandemic left its mark not only on public health but also on society at large. Sociological insights about the changes in, for example, inequality, sociability and social resilience are becoming increasingly clear now that the onset of the pandemic is further behind us. In this volume, sociologists and science press from related disciplines shine their light on the challenges of our time. In doing so, they focus on three questions: 1) what do we know about the social consequences of corona?, 2) what do we disagree on as scientists? and 3) what does the pandemic teach us about large-scale challenges in the future? Using the insights from this volume, we illuminate sociological issues and provide direction for the future.